Index of Functional Changes in the Assessment Adaptive State of Comorbid Patients Treated with Trimetazidine - Normatov Murod Buribayevich (Peerian Journals Publishing, 2022)
The development of myocardial ischemia and the rapid progression of atherosclerosis in patients with type 2 diabetes mellitus (DM) with the formation of diabetic autonomic cardiac neuropathy contributes to the aggravation of the prognosis of the course of cardiovascular diseases (CVD). For example, dyslipidemia with type 2 diabetes occurs in 2, and arterial hypertension is 3 times more common than without it. At the same time, it is believed that the impact of any risk factor on the level of cardiovascular mortality in diabetic patients is 3 times higher than in people without diabetes. Thus, changes in the metabolism of cardiomyocytes in ischemia can be considered as a point of application of drug effects, in particular with the help of drugs that can directly affect cellular metabolism. One of such approaches is the use of drugs from the group of so-called myocardial cytoprotectors, in particular trimetazidine. Cardiovascular diseases (CVD) are the main cause of death in patients with type 2 diabetes mellitus (DM2). In people suffering from DM2, the risk of developing CVD is 2-5 times higher than in people with normal carbohydrate metabolism. Hyperglycemia, insulin resistance and hyperinsulinemia are considered among the reasons that increase the risk of developing CVD in DM 2. Hyperglycemia is a factor that disrupts the functioning of the endothelium, which leads toincreased platelet adhesion and aggregation, increased coagulation risk factors in the bloodstream. Insulin resistance increases the synthesis of a type I inhibitor of plasminogen activators, which inhibits fibrinolytic activity of blood plasma. Trimetazidine (TMZ) is a representative of metabolic drugs. Its effect is associated with inhibition of oxidation of free fatty acids (FFA). Taking into account the violation of the metabolism of cardiomyocytes in DM and especially when combined with coronary artery disease, given the evidence of the effectiveness of TMZ in patients with stable angina, it can be assumed that the use of TMZ will be especially effective in the treatment of patients with coronary heart disease in combination with disorders of carbohydrate metabolism. Polymorbidity, impaired function of internal organs (kidneys, liver, gastrointestinal tract), age-related metabolic features affect the pharmacokinetic parameters of drugs, which reduces the effectiveness of treatment and increases the risk of adverse effects (ND) of drugs. In elderly patients, as a rule, polypragmasia occurs, sometimes as an inevitable consequence of polymorbidity. At the same time, the risk of developing ND pharmacotherapy in elderly patients is 5-7 times higher than in younger patients, and they are more severe. The incidence of ND is proportional to the number of medications taken and ranges from 10% when taking 1 drug to 100% when taking 10 medications. At the same time, it should be remembered that vitamins, phytopreparations, dietary supplements also cause the development of ND and drug interactions.
Keywords: coronary heart disease; diabetes mellitus; trimetazidine